Accurate Theoretical Models for Frequency Diverse Array Based Wireless Power Transmission - Zeeshan Ahmad; Zhonghan Wang; Zain ul Abidin Jaffri; Shudi Bao (Energies, 2022)
Wireless power transfer (WPT) is a well-known problem, and has received wide attention in the next generation industrial applications and consumer electronics. On the other hand, frequency diverse array (FDA) is a new concept with the ability to generate a range-angle dependent beampattern. Therefore, some researchers are engaged in designing WPT systems based on the FDA framework (FDA-WPT) instead of phased arrays. Unlike phased arrays, the FDA beampattern is time-variant. Therefore, existing beam collection efficiency models based on the phased array are not suitable for the FDA-WPT system. More importantly, the time-variant property of FDAs is usually ignored in the literature, and the system configuration of the target area where the power-harvesting end is located does not conform to the actual WPT scenario. In this paper, we derive and present accurate models of the FDA-WPT system. The power transfer performance of the corrected FDA-WPT system is then compared with the phased array based WPT system. Simulation results demonstrate that time-variant consideration in the FDA-WPT model causes difficulty in controlling the main beam direction to focus the power. The accurate FDA-WPT is theoretically investigated, and numerical simulations are implemented to validate the theoretical analysis.